Investigation of the conduction processes in PZT-based multiferroics: Analysis from Jonscher's formalism - Guerra, J. D. S.; Portugal, R. J.; Silva, A. C. [UNESP]; Guo, R.; Bhalla, A. S. (Wiley-Blackwell, 2014)
The conductive processes in multiferroic ceramic composites based on PbZr0.65Ti0.35O3 (PZT) and BaFe12O19 (BaM), synthesized by the conventional solid-state reaction method, have been investigated. The DC and AC electrical conductivities have been analyzed in a wide temperature and frequency range and the influence of the BaM content on the electrical properties of the PZT-xBaM composites has been taken into account. It has been observed that the inclusion of the BaM in the PZT ferroelectric matrix promotes conduction mechanisms with magnetic-order characteristics on the ceramics, which were related to doubly ionized oxygen vacancies, superexchange, and double-exchange-type interactions. The obtained results are discussed in the framework of Jonscher's formalism.
Keywords: ceramic materials; conduction mechanisms; electrical properties; ferroelectrics; multiferroics